Development of PMAxxTM-Based qPCR for the Quantification of Viable and Non-viable Load of Salmonella From Poultry Environment - Zhang, Jiawei; Khan, Samiullah; Chousalkar, Kapil K. (Frontiers in Microbiology, 2020)
Determining the viable and non-viable load of foodborne pathogens in animal production can be useful in reducing the number of human outbreaks. In this study, we optimized a PMAxxTM-based qPCR for quantifying viable and non-viable load of Salmonella from soil collected from free range poultry environment. The optimized nucleic acid extraction method resulted in a significantly higher (P < 0.05) yield and quality of DNA from the pure culture and Salmonella inoculated soil samples. The optimized primer for the amplification of the invA gene fragment showed high target specificity and a minimum detection limit of 102 viable Salmonella from soil samples. To test the optimized PMAxxTM-based qPCR assay, soil obtained from a free range farm was inoculated with Salmonella Enteritidis or Salmonella Typhimurium, incubated at 5, 25, and 37°C over 6 weeks. The survivability of Salmonella Typhimurium was significantly higher than Salmonella Enteritidis. Both the serovars showed moisture level dependent survivability, which was significantly higher at 5°C compared with 25°C and 37°C. The PMAxxTM-based qPCR was more sensitive in quantifying the viable load compared to the culture method used in the study. Data obtained in the current study demonstrated that the optimized PMAxxTM-based qPCR is a suitable assay for quantification of a viable and non-viable load of Salmonella from poultry environment. The developed assay has applicability in poultry diagnostics for determining the load of important Salmonella serovars containing invA.